Representasi Citra Perempuan dalam Cerita Rakyat Dayak Kenyah Tilo Enggau - Jogarni Maria Marta; Nina Queena Hadi Putri (Badan Pengembangan dan Pembinaan Bahasa, 2025)
This study aims to reveal the image of women in the Tilo Enggau folktale from the Dayak Kenyah community as a symbolic, spiritual and socio-cultural discourse. This study uses a qualitative approach with data collection techniques in the form of in-depth interviews with informants from the Dayak Kenyah community and documentation of unpublished folklore texts as objects of study. The data were analyzed using three feminist perspectives: radical feminism, cultural feminism and ecofeminism. The results of the study show that the female characters in the story appear as independent figures who reject the norms of marriage, experience supernatural pregnancies and give birth to descendants from heaven. The female characters in this story not only carry out biological functions, but also represent strong socio-cultural constructions. Women are the center of lineage and have symbolic authority as guardians of social harmony. This representation is emphasized through the sacred ancestral speech